2021
DOI: 10.1088/1755-1315/735/1/012086
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent, Nano-fertilizers: A New Technology for Improvement Nutrient Use Efficiency (Article Review)

Abstract: Nano fertilizers are essential resources in agriculture in order to increase crop production, quality, productivity, and boost nutrient uptake. Nano-fertilizer is efficient for specific use of nutrients at appropriate time of plant growth and can provide nutrients as a whole with the crop. Growing crops with heavier fertilizer concentrations further increases may be limiting to crop growth due to nutrient toxicity. Nano-fertilizers provide more area for photosynthesis, leading to more sunlight absorption and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Aside from organic and synthetic fertilizers, the agricultural industry is today supported by the presence of new technologies, namely nano fertilizers. Nanotechnology offers the ability to create slow-release, high-efficiency nanofertilizers [281] that enhance soil nutrients, create healthier soil ecosystem, improve microbial communities [282] and thereby lowering cultivation expenses. Study by Rajput [283] showed that the population of soil microbial communities exposed to nanofertilizer was much higher than in soil amended with chemical fertilizer.…”
Section: Fertilizermentioning
confidence: 99%
“…Aside from organic and synthetic fertilizers, the agricultural industry is today supported by the presence of new technologies, namely nano fertilizers. Nanotechnology offers the ability to create slow-release, high-efficiency nanofertilizers [281] that enhance soil nutrients, create healthier soil ecosystem, improve microbial communities [282] and thereby lowering cultivation expenses. Study by Rajput [283] showed that the population of soil microbial communities exposed to nanofertilizer was much higher than in soil amended with chemical fertilizer.…”
Section: Fertilizermentioning
confidence: 99%
“…The results in Table (3), it was found that the increase in plant height when spraying nanomaterials and silica fertilizer, and this is due to the fact that nanomaterials lead to stimulating growth, increasing photosynthesis and increasing the plant's tolerance to biotic and abiotic stresses , it has a high surface area and a high speed of penetration and representation [13]. and that silica fertilizer has a role in the process of erection of the rice stalk and its branches, which is important in the process of photosynthesis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its positive effects on crop nutrition quality and stress reduction in plants and the lack of added quantities and costs due to the speed of their absorption by the roots, due to the large surface area compared to the volume and its rapid penetration into cells and plant tissues with the possibility of smart targeting, slow-release, and speed of transport [12]. Nano-fertilizers provide some nutrients with slow release and minutes with diameters less than (1-100) nanometers where they promote plant growth and production [13]. Titanium is an interesting chemical element, especially from a physiological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of high is that chemical fertilization operation has a massive influence on the physiological properties of the plant by raising photosynthesis elements, which also results in higher in the root collective and its secretions, which attract organisms generating types of enzymes, and the secretions of the roots themselves and the role of seaweed extracts in ensuring the utilization of aspects food, It plays an essential part in the excretion of some enzymes, growth organizers, and plant hormones, and its significance to the plant, it also plays a major role in impacting soil biology by providing energy and some elements required to build bodies and bring out reproduction and external physiological functions. The efficiency of microorganisms is directly connected to the enzyme [36,37,38]. The effect of the bi-interaction between the addition of urea and seaweed extracts on the activity of urease enzyme µg N-NH 4 + g -1 soil2h -1 of the reducing layer in the period of full maturity showed significant differences.…”
Section: The Activity Of Urease For the Two Layers Of Oxidation And R...mentioning
confidence: 99%